Religious pluralisation in Slovenia - Črnič, Aleš (Teorija in praksa, 2013)
The article analyses the dynamics of religious pluralisation in Slovenia. Historical developments in various states have kept Slovenians almost exclusively within the Roman-Catholic Church, except for a short Reformation period. The socialist after-war secularisation of society has in many respects undermined the Catholic monopoly, but it failed to create an open religious market. In the transitional period the statistics of Catholics continued to drop, and at the same time ever more new religious movements emerged. These are mostly very small and at the time being do not show the potential for substantial growth. The article analyses in detail religious pluralisation in the regions of Ljubljana and Nova Gorica.
Keywords: Pluralism; Pluralizem; Religious communities; Secularization; Sekularizacija; Slovenia; Slovenija; Verske skupnosti; verski pluralizem